2011
DOI: 10.1161/hypertensionaha.111.174359
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use β-Blocking Agents in Patients With Peripheral Artery Disease?

Abstract: See related article, pp 148 -154 P eripheral artery disease (PAD) has been for many years a chapter in cardiovascular diseases that did not attract the interest of clinicians. Intermittent claudication, the most common clinical manifestation of PAD, was considered a rather unimportant symptom. Several new findings published during the last decade have profoundly changed our views on PAD. 1 First, intermittent claudication significantly impacts on the quality of life and on the activities of the patients experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of the current study revealed not only the association between CaCBs and periodontitis but also that β antagonists and polystyrene sulphonate could contribute to the development of periodontitis. The occurrence of vasoconstriction and ischaemia due to the use of β antagonists by blocking β2 dependent vasodilatation which causes peripheral α−1 predominance is a well‐known entity in patients with peripheral artery disease (Clement ). Similar to the peripheral effect, it may also cause decreased blood flow in oral mucosa and facilitate bacterial overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study revealed not only the association between CaCBs and periodontitis but also that β antagonists and polystyrene sulphonate could contribute to the development of periodontitis. The occurrence of vasoconstriction and ischaemia due to the use of β antagonists by blocking β2 dependent vasodilatation which causes peripheral α−1 predominance is a well‐known entity in patients with peripheral artery disease (Clement ). Similar to the peripheral effect, it may also cause decreased blood flow in oral mucosa and facilitate bacterial overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there was a concern that beta blockers can result in peripheral hemodynamic compromise by upregulating alpha adrenergic drive due to blockage of beta-2 dependent vasodilation resulting in vasoconstriction and limb ischemia [59]. However, patients with PAD have high prevalence of concomitant coronary artery disease and other indications for beta-blockers.…”
Section: Beta-blockersmentioning
confidence: 99%